PELAKSANAAN JARING PENGAMAN SOSIAL BAGI LANSIA DAN PENYANDANG DISABILITAS BERAT MELALUI PROGRAM KELUARGA HARAPAN DI KECAMATAN KEMLAGI KABUPATEN MOJOKERTO - Miftakhul Jannah; Singgih Manggalou (Halu Oleo University, 2025)
This study aims to analyse the implementation of PKH for elderly and severely disabled beneficiaries in Kemlagi District, Mojokerto Regency, which has one of the highest numbers of recipients in the region. A qualitative descriptive method was applied, focusing on three elements of implementation based on David C. Korten’s theory: the program, the implementing organisation, and beneficiaries. Data were collected through interviews with the Mojokerto Social Affairs Office, PKH facilitators, and beneficiary households (KPM), complemented by documentation and field observations. The findings reveal that PKH has generally succeeded in improving living standards, encouraging self-reliance, and reducing poverty, although the amount of assistance remains insufficient to fully cover household needs. The implementing organisations are considered effective due to multi-level coordination from national to village levels, although the limited number of facilitators poses challenges. Beneficiary targeting and data collection largely follow regulations, yet issues of mistargeting remain due to weak initial validation. In conclusion, PKH plays a significant role in providing social protection for the elderly and severely disabled groups, but improvements in data accuracy, validation, and facilitation are needed to optimise program outcomes.